2006
DOI: 10.1074/jbc.m602423200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Route for F-box Protein-mediated Ubiquitination Links CHIP to Glycoprotein Quality Control

Abstract: In SCF (Skp1/Cullin/F-box protein) ubiquitin ligases, substrate specificity is conferred by a diverse array of F-box proteins. Only in fully assembled SCF complexes, it is believed, can substrates bound to F-box proteins become ubiquitinated. Here we show that Fbx2, a brain-enriched F-box protein implicated in the ubiquitination of glycoproteins discarded from the endoplasmic reticulum, binds the co-chaperone/ubiquitin ligase CHIP (C terminus of Hsc-70-interacting protein) through a unique N-terminal PEST doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 35 publications
7
44
1
Order By: Relevance
“…On the cooperativity of CHIP with other E3s, two action modes have been proposed: 1) in neurons, CHIP acts with Fbx2 in glycoprotein quality control, where an NH 2 -terminal PEST sequence interacts with the TPR domain of CHIP to facilitate the F-box associated domain (FBA)-high mannose glycoprotein interaction (22), and 2) in the Notch-induced degradation of Tal1/SCL, where both CHIP and Skp2 can bind Tal1 (23). The latter case bears some similarity with the current study in that the substrate (GHR) binds two E3s, independently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the cooperativity of CHIP with other E3s, two action modes have been proposed: 1) in neurons, CHIP acts with Fbx2 in glycoprotein quality control, where an NH 2 -terminal PEST sequence interacts with the TPR domain of CHIP to facilitate the F-box associated domain (FBA)-high mannose glycoprotein interaction (22), and 2) in the Notch-induced degradation of Tal1/SCL, where both CHIP and Skp2 can bind Tal1 (23). The latter case bears some similarity with the current study in that the substrate (GHR) binds two E3s, independently.…”
Section: Discussionmentioning
confidence: 99%
“…Given the role of CHIP in ERAD, it is important to investigate a possible role in GHR synthesis and maturation (22,34,35). Previously, we showed that the GHR is efficiently folded in the endoplasmic reticulum (36).…”
Section: Ubc13 and Chip Involved In Ghr Endocytosismentioning
confidence: 99%
“…RbcS [02]:GFP and T7:Hsc70-4 were transformed into protoplasts together with T7:CHIP or T7:TPR, and Hsc70-4-mediated protein degradation was examined in the protoplasts. TPR, a deletion mutant that contains only the N-terminal TPR domain of CHIP (which interacts with Hsp70; Nelson et al, 2006), was included as a dominant-negative mutant ). Coexpression of both T7:CHIP and T7:Hsc70-4 slightly further increased the extent of Hsc70-4-induced reporter protein degradation compared with the expression of T7:Hsc70-4 alone ( Figure 8C, compare lane 5 …”
Section: Chip Interacts With Hsc70-4 and Is Involved In Hsc70-4-mediamentioning
confidence: 99%
“…[19][20][21] While Skp2 and many other ubiquitin ligases recognize phosphorylated substrates, the FBG family, comprised of FBG1-5, is unique in that it recognizes glycosylated proteins. [22][23][24][25][26][27] In previous studies, we found that overexpressing FBG1 in CHO cells resulted in growth arrest. 28 We and others also previously showed that FBG1 had a relatively low affinity for the SCF scaffold protein Cul1; in fact, rather than forming the canonical SCF complex, FBG1 primarily formed a dimer with Skp1.…”
Section: Fbg1 Interacts With Different Cullinmentioning
confidence: 99%
“…In our earlier work we noted that FBG1 had a low affinity for the SCF scaffold protein, Cul1. 22,23,33 In fact, rather than forming the canonical SCF complex, it primarily formed a dimer with Skp1. Since Cul7 is the only other known cullin that binds F-box proteins ( Fig.…”
Section: Fbg1 Interacts With Different Cullinmentioning
confidence: 99%